2011
DOI: 10.1089/jir.2010.0120
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Role of RNase L in Innate Immunity

Abstract: The interferon (IFN)-inducible 2 0 -5 0 -oligoadenylate synthetase (OAS)/RNase L pathway blocks infections by some types of viruses through cleavage of viral and cellular single-stranded RNA. Viruses induce type I IFNs that initiate signaling to the OAS genes. OAS proteins are pathogen recognition receptors for the viral pathogenassociated molecular pattern, double-stranded RNA. Double-stranded RNA activates OAS to produce p x 5 0 A(2 0 p5 0 A) n ; x ¼ 1-3; n > 2 (2-5A) from ATP. Upon binding 2-5A, RNase L is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
270
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 279 publications
(276 citation statements)
references
References 90 publications
(13 reference statements)
5
270
0
1
Order By: Relevance
“…For example, protein kinase R (PKR) is activated by dsRNA and phosphorylates the alpha subunit of eukaryotic initiation factor 2 (eIF2␣), blocking translation initiation (61). The enzyme 2=-5=-oligoadenylate synthase (2=5=OAS) also is activated by dsRNA to produce 2=-5=-adenylic acid, which stimulates RNase L to degrade cellular RNA (11). These and other mechanisms prevent virus replication in infected cells and prime neighboring cells to enter a refractory antiviral state.…”
mentioning
confidence: 99%
“…For example, protein kinase R (PKR) is activated by dsRNA and phosphorylates the alpha subunit of eukaryotic initiation factor 2 (eIF2␣), blocking translation initiation (61). The enzyme 2=-5=-oligoadenylate synthase (2=5=OAS) also is activated by dsRNA to produce 2=-5=-adenylic acid, which stimulates RNase L to degrade cellular RNA (11). These and other mechanisms prevent virus replication in infected cells and prime neighboring cells to enter a refractory antiviral state.…”
mentioning
confidence: 99%
“…It was described in 1995 as RNase-L inhibitor (RLI1) on the basis of its coimmunoprecipitation with RNase-L and inhibitory effect on RNase-L mediated RNA degradation (Bisbal et al , 1995 ). RNase-L is an interferon-dependent polysome-associated antiviral defense enzyme that is activated by 2 ′ -5 ′ oligoadenylates and degrades mRNA and single-stranded viral RNA in virus infected cells (Silverman , 2007 ), but also has a variety of additional functions (Chakrabarti et al , 2011 ). In 2002, ABCE1 was found to be required for the assembly of immature HIV-1 capsids and it has been suggested that it accounts for the ATP dependence of the rather poorly understood capsid assembly process (Zimmerman et al , 2002 ).…”
Section: Abc Enzymes: Versatile Molecular Machines or Switchesmentioning
confidence: 99%
“…RNASEL is a putative tumor-suppressing enzyme that may inhibit growth and proliferation and induce apoptosis (10)(11)(12), and is implicated in the cleavage of viral RNA and the interferonmediated immune response (13). Polymorphisms in RNASEL, located on chromosome 1q25, have been inconsistently linked to hereditary and general prostate cancer risk (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%